Progressive hemifacial atrophy Parry Romberg syndrome characteristics of craniofacial morphology - Nikodijević-Latinović Angelina (Serbian Medical Society - Dental Section, Belgrade, 2007)
The aim of this case report was to analyze clinical finding in a patient with rare, Parry Romberg syndrome. The patient was diagnosed with progressive facial hemiatrophy that affected skin, subcutaneous tissue and underlying bony structures. Analysis of study models and cephalometric radiographs confirmed there was insufficient development of the facial right side: asymmetric narrow upper jaw, shorter mandibular ramus and corpus, upper frontal teeth asymmetry, crowding of the upper dental arch on the right side. An orthodontic treatment plan was proposed within the entire rehabilitation program that included collaboration with a maxillofacial and plastic surgeon.